Management of advanced adult congenital heart disease - Bowater, Sarah E. (SA Heart Journal, 2017)
There are increasing numbers of adults with congenital heart disease. These patients remain at lifelong risk of complications including heart failure, arrhythmias and premature death. This review examines the management of those patients with advanced disease, with particular reference to patients with either a systemic right ventricle or a univentricular circulation. Drugs used to treat left ventricular dysfunction in acquired heart disease have been shown to have little benefi t in this setting. There are, however, promising results from small trials looking at selective pulmonary vasodilators in patients with a previous Fontan operation. Whilst there is evidence of a benefi t with implantable cardiac defi brillators and cardiac resynchronisation, there remains a lack of clear guidelines as to which patients will benefi t from these invasive therapies. Cardiac transplantation in these patients is associated with an increased early mortality but the long term outcome is similar to those with acquired heart failure. Transplantation however, is limited by both the patient’s suitability and the availability of a matched organ. End of life care should be discussed with all patients with advanced disease and ideally this should be done early on and in parallel to other therapies.